An investigation into gamma radiation shielding parameters of the (Al:Si) and (Al+Na):Si-doped international simple glasses (ISG) used in nuclear waste management, deploying Phy-X/PSD and SRIM software - Kamislioglu, M. (Journal of materials science. Materials in electronics, 2021)
Nuclear power plants that produce sustainable energy are the most striking examples of generating carbon-free energy. However, nuclear power plants demand the safe management of nuclear waste. The radiation tests of the materials, which are used in successful waste management in nuclear power plants, must be carried out. In this study, the radiation interaction parameters were examined of International simple glasses (ISG) with superior properties, used in nuclear waste management. The gamma radiation shielding properties of the (Al:Si) and (Al + Na):Si-dopped ISG glasses were investigated using Photon Shielding and Dosimetry (Phy-X / PSD) software for the selected energy range. LAC, MAC, MFP, HVL, TVL, Z eff , N eff , C eff Z eq , EBF, EABF and FNRCS calculations were applied to assess the radiation protection parameters by Phy-X/PSD software. In addition, MSP and PR (H 1 , He +2 ) values were calculated by SRIM software. Also, each obtained parameter provided us with so important information on radiation protection, and these methods have been used frequently in the literature. Substituting an atomic fraction of (Al:Si) with (Al + Na):Si resulted in a reduction of the total atomic cross-section of the glass, which lowered the MAC. The obtained results showed that the highest MAC value belong to ISG-A00N glass. The MAC value gradually decreased as the Al, Na and Si contents increased. Likewise, the HVL, TVL and MFP values changed coherent with this. Moreover, Z eff and N eff values were seen in the ISG-A00N sample to take the maximum values to each other inversely. The most effective glass sample turned out to be ISG-A00N glass at the mean free path penetration power of MSP and PR values. Computations were made for glasses with SiO 2 , Al 2 O 3 , B 2 O 3 , Na 2 O, CaO and ZrO 2 content given with ISG-C, ISG-A00, ISG-A12, ISG-A22, ISG-A00N, ISG-A11N, ISG-A18N and ISG-A23N codes. When all the results were evaluated, ISG-A00N glass which has the highest Si and Ca contents and density was found to be the glass with the best radiation shielding feature. It is also noteworthy that this glass does not contain any Al component. As the results of the investigation, it was found out that such a small doped of the Si increases the radiation shielding feature of the glass. The obtained results have revealed that the ISG-A00N > ISG-A00 > ISG-C > ISG-A12 > ISG-A11N > ISG-A22 > ISG-A18N > ISG-A23N samples, in ascending order that attenuators for low energy radiations.